2014
DOI: 10.1002/jip.1422
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Rapists' Motivations as Illustrated by Their Crime Scene Actions: Is the Gender of the Victim an Influential Factor?

Abstract: An aim of this paper was to examine if the rapist's motivations of anger and power as inferred from rape crime scene behaviours differentiates between rape victim genders. In addition, it was sought to analyse the resistance strategies employed by rape victims to investigate whether gender influences victim-offender behavioural interactions. A sample of 24 female and 12 male rape victims aged from 13 to 39 years were analysed. The data were extracted from the US National Crime Survey, which contained 12 report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Research by Lees (1997) of 85 victim and 81 police reports of male rape found that the threat of violence was often sufficient to gain compliance from the victims. Jamel (2001), in her comparison of 24 female and 12 male rape victims, found a difference in relation to both the level and timing of violence. Overall, male victims experienced less violence than female victims and female victims tended to experience violence during an attack while male victims experienced violence at the outset of an attack.…”
Section: Male Rape Researchmentioning
confidence: 96%
“…Research by Lees (1997) of 85 victim and 81 police reports of male rape found that the threat of violence was often sufficient to gain compliance from the victims. Jamel (2001), in her comparison of 24 female and 12 male rape victims, found a difference in relation to both the level and timing of violence. Overall, male victims experienced less violence than female victims and female victims tended to experience violence during an attack while male victims experienced violence at the outset of an attack.…”
Section: Male Rape Researchmentioning
confidence: 96%
“…Misogyny is characterized as leading to a sense of male entitlement, where men feel entitled to women’s bodies and feminine-coded goods such as emotional labor and domestic housework; when women do not meet these expectations or violate the rules of patriarchy, men may retaliate through aggression and sexual violence as a way of reclaiming their dominance (Manne, 2017). Researchers have found similar patterns by analyzing interviews of sexual assault victims to determine the motivations of the perpetrator; the interviews suggested that the primary motivation for perpetrators against women was power (Jamel, 2014). From the patterns observed in the interviews, the reseacher speculated that sexual assault committed against women may be driven by a need to control women, feeling entitled to sex, and feelings of inadequacy in one’s own masculinity.…”
Section: Sexism Misogyny and Sexual Assaultmentioning
confidence: 97%
“…of sexual assault victims to determine the motivations of the perpetrator; the interviews suggested that the primary motivation for perpetrators against women was power (Jamel, 2014). From the patterns observed in the interviews, the reseacher speculated that sexual assault committed against women may be driven by a need to control women, feeling entitled to sex, and feelings of inadequacy in one's own masculinity.…”
Section: Researchers Have Found Similar Patterns By Analyzing Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stermac et al ., ) while others find the opposite (e.g. Jamel, ) and yet others find no difference (e.g. Woodhams, Gillett, & Grant, ).…”
Section: Introductionmentioning
confidence: 97%